The influence of Socio-Economic Factors to Red Guava Farming Income in The Yard (Case Study: in Trirenggo Village, Bantul District, Bantul Regency) - Reo Sambodo; Wafit Dinarto (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2022)
Red guava has many advantages, so it is the right choice as a mainstay commodity in agricultural development with a creative approach to agribusiness innovation. The purpose of this study was to analyze the socio-economic influence of guava farm income and to analyze the income of guava farm in the yard. To analyze the influence of socio-economic factors used multiple linear regression analysis. The results showed that socio-economic factors including family dependents (X1), capital (X2), land area (X3), experience (X4) affect the income of guava farming, while the age factor does not affect the income of guava farming. By using the income formula obtained by the average net income of Mr. June farm amounted to Rp. 4,069,683/month.